Revitalization of Environmentally Friendly Pinisi PELRA Fleet as a Feeder for Perintis Routes in 3TP Areas - Praditya, Antonius Hendrawan Tio; Widjaja, Sjarief; Pribadi, Triwilasndio Wuruk (International Journal of Marine Engineering Innovation and Research, 2025)
Pelra Pinisi ships are increasingly being abandoned in freight transportation to 3TP (disadvantaged, outermost, remote, and border) regions, which are now predominantly served by perintis vessels. Unlike these perintis vessels, Pelra Pinisi ships do not receive similar government subsidies and face limitations in navigating currents and sea waves. This study proposes the revitalization of Pelra Pinisi ships through the implementation of a soft sail design to reduce emissions and fuel consumption, optimal route determination using a solver, and subsidy calculations to ensure competitiveness. The study was conducted in East Nusa Tenggara, covering six perintis routes and 24 ports. Survey data indicate that traditional Pelra vessels typically range from 30 to 40 meters in length. The proposed new designs include ships of 300 GT, 200 GT, and 100 GT, with lengths of 35.00 m, 22.75 m, and 17.50 m, respectively, and speeds of 12.5 knots, 7.8 knots, and 6.0 knots. Emission reductions were observed on the Kupang–Ndao and Kupang–Naikliu routes by 0.89%. The 300 GT vessel is optimal for the Kupang–Ndao and Labuan Bajo–Maumbawa routes, the 200 GT vessel for the Sabu–Raijua and Waikelo–Labuan Bajo routes, and the 100 GT vessel for several other routes.